2021
DOI: 10.1038/s41419-021-04149-x
|View full text |Cite
|
Sign up to set email alerts
|

KLK8 promotes the proliferation and metastasis of colorectal cancer via the activation of EMT associated with PAR1

Abstract: Kallikrein-related peptidase 8 (KLK8) acts as an oncogene or anti-oncogene in various tumours, and the abnormal expression of KLK8 is involved in the carcinogenesis of several tumours. However, the role of KLK8 in colorectal cancer (CRC) and the underlying mechanism remain largely unclear. In this study, the carcinogenic effect of KLK8 was determined via CCK-8 and colony formation assays in vitro and a xenograft model in nude mice in vivo. The metastasis-promoting effect of KLK8 was investigated with transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…KLK8 has high expression in a variety of tumors including pancreatic and colorectal cancer. In experimental mouse models, KLK8 overexpression had both pro-proliferative and anti-apoptotic effects [49, 50]. The FKBP4 gene is a member of the immunophilin protein family, which play a role in immunoregulation and basic cellular processes involving protein folding and trafficking.…”
Section: Resultsmentioning
confidence: 99%
“…KLK8 has high expression in a variety of tumors including pancreatic and colorectal cancer. In experimental mouse models, KLK8 overexpression had both pro-proliferative and anti-apoptotic effects [49, 50]. The FKBP4 gene is a member of the immunophilin protein family, which play a role in immunoregulation and basic cellular processes involving protein folding and trafficking.…”
Section: Resultsmentioning
confidence: 99%
“…KLK8 induced colorectal cancer development by triggering EMT [256]. The wound healing and Transwell migration assays revealed that KLK8 promoted cell proliferation, invasion and metastasis [256]. The upregulation was also associated with metastasis of head and neck SCC to cervical lymph nodes [257].…”
Section: Metastasis-regulated Differentially Expressed Genesmentioning
confidence: 99%
“…Kallikrein-related peptidase 8 (KLK8) is one such protein that has been identified to be highly expressed in cervical, ovarian and endometrial cancers, indicating that it could be a viable target for therapy [254,255]. KLK8 induced colorectal cancer development by triggering EMT [256]. The wound healing and Transwell migration assays revealed that KLK8 promoted cell proliferation, invasion and metastasis [256].…”
Section: Metastasis-regulated Differentially Expressed Genesmentioning
confidence: 99%
“…In another d-flow-related study, ( Li F. et al, 2021 ) also found that d-flow induced EC transformation into pro-atherogenic phenotypes. Several EC subsets have been identified, which highly express Klk8 (a secretory serine protease, acting as an oncogene or anti-oncogene in various tumors and associated with learning and memory), Lrp1(LDL receptor-related protein 1, associated with lipid homeostasis, clearance of apoptotic cells and metabolism of amyloid-β peptides), Dkk2 (dickkopf WNT signaling pathway inhibitor 2, related to angiogenesis) and Cd36 (a scavenger receptor associated with lipid metabolism) respectively, namely Klk8 hi , Lrp1 hi , Dkk2 hi , and Cd36 hi ECs ( Endemann et al, 1993 ; Min et al, 2011 ; Shinohara et al, 2017 ; Li J. et al, 2021 ; Hua et al, 2021 ). Klk8 hi and Lrp1 hi ECs are mainly derived from non-PCL carotid arteries, whereas Dkk2 hi and Cd36 hi ECs are d-flow-derived EC subsets.…”
Section: Scrna-seq Applications In Atherosclerosis Researchmentioning
confidence: 99%